A Life‐Design‐Based Online Career Intervention for Early Adolescents: Description and Initial Analysis. Issue 1 (March 2016) - Nota, Laura; Santilli, Sara; Soresi, Salvatore
Abstract : Using contemporary digital technology offers possibilities for better engaging youth in constructing their future careers. This study describes and initially tests the effectiveness of an online career intervention based on life‐design principles. Middle school students were assigned to either a traditional test interpretation‐based intervention group or an online intervention group. Analysis conducted to evaluate pre‐ and posttest differences between the 2 groups indicated that students in the online intervention group showed higher levels of career adaptability and life satisfaction than did students in the traditional intervention group. Results also suggested that intervention increased students' narratives future aspirations.